2016
DOI: 10.1038/pr.2016.164
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal growth restriction augments oxygen-induced pulmonary hypertension in a neonatal rat model of bronchopulmonary dysplasia

Abstract: PNGR induces right ventricular and pulmonary vascular remodeling and augments the effects of oxygen in neonatal rats. This may be a powerful tool to investigate the mechanisms that induce PH in low-birth-weight preterm infants with BPD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 41 publications
9
28
0
Order By: Relevance
“…After birth, pups were pooled and randomly assigned to litters of 10 pups (normal litter size, N) or 17 pups (restricted litter size, R). Additionally, pups were randomly assigned to cages maintained in room air (A) or exposed to 75% oxygen (O) in a plexiglass chamber (Biospherix, Lacona, NY, United States) continuously, and dams were rotated with the appropriate control or PNGR dam every 24 h. As we have shown previously, the pups tolerate hyperoxia for 14 days without mortality (12). Some pups in each group were injected subcutaneously with the TLR4 inhibitor TAK-242 (Cayman Chemicals, Ann Arbor, MI, United States) (Resatorvid, 3 mg/kg/day from birth) or with vehicle alone (5% ethanol).…”
Section: Animalsmentioning
confidence: 99%
See 3 more Smart Citations
“…After birth, pups were pooled and randomly assigned to litters of 10 pups (normal litter size, N) or 17 pups (restricted litter size, R). Additionally, pups were randomly assigned to cages maintained in room air (A) or exposed to 75% oxygen (O) in a plexiglass chamber (Biospherix, Lacona, NY, United States) continuously, and dams were rotated with the appropriate control or PNGR dam every 24 h. As we have shown previously, the pups tolerate hyperoxia for 14 days without mortality (12). Some pups in each group were injected subcutaneously with the TLR4 inhibitor TAK-242 (Cayman Chemicals, Ann Arbor, MI, United States) (Resatorvid, 3 mg/kg/day from birth) or with vehicle alone (5% ethanol).…”
Section: Animalsmentioning
confidence: 99%
“…At day 14, echocardiography was performed on pups under light anesthesia with isoflurane using a VisualSonics VIVO 2100 in vivo ultrasound imaging system (VisualSonics, Toronto, ON, Canada) to determine the ratio of the pulmonary acceleration time (PAT) to the total ejection time (ET) a marker of PH as previously described (12).…”
Section: Echocardiographymentioning
confidence: 99%
See 2 more Smart Citations
“…Further, the postnatal growth restriction resulting from insufficient total calories that is commonly observed in premature infants 98, 99 may represent an additional risk factor 100 , with evidence suggesting that adequate intake of protein 101 , fat 102 , and specific vitamins 103106 are particularly important. Data from animals models 107109 suggest that pre- and postnatal growth restriction alters antioxidant activity 110 , surfactant production 111 , pulmonary endothelial function 112 , and biologic pathways that regulate pulmonary vascular growth 113 . Despite these broad effects on key developmental pathways, recent clinical trials to optimize nutrition in preterm infants have demonstrated little or no impact on the incidence of BPD 114117 , with the exception of Vitamin A supplementation, which is associated with a small decrease in the risk of developing BPD 118 .…”
Section: Injurious Stimuli That Disrupt Late Lung Developmentmentioning
confidence: 99%